High sensitivity of gross primary production in the Rocky Mountains to summer rain. Issue 8 (30th April 2017) - Berkelhammer, M.; Stefanescu, I. C.; Joiner, J.; Anderson, L.
Abstract: In the catchments of the Rocky Mountains, peak snowpack is declining in response to warmer spring temperatures. To understand how this will influence terrestrial gross primary production (GPP), we compared precipitation data across the intermountain west with satellite retrievals of solar‐induced fluorescence (SIF), a proxy for GPP. Annual precipitation patterns explained most of the spatial and temporal variability of SIF, but the slope of the response was dependent on site to site differences in the proportion of snowpack to summer rain. We separated the response of SIF to different seasonal precipitation amounts and found that SIF was approximately twice as sensitive to variations in summer rain than snowpack. The response of peak GPP to a secular decline in snowpack will likely be subtle, whereas a change in summer rain amount will have precipitous effects on GPP. The study suggests that the rain use efficiency of Rocky Mountain ecosystems is strongly dependent on precipitation form and timing. Key Points: Solar‐induced fluorescence shows clear response to variability in precipitation across Rocky Mountains The GPP response to summer precipitation variability is twice as strong as for variability in winter snowpack Rocky Mountain ecosystems will increase rain use efficiency in response to future decreases in the ratio of winter to summer precipitation